Prevalence of High-Risk HPV Subtypes and Efficacy of the HPV Vaccine in Preventing Cervical Epithelial Lesions: Survey and Insights from a German Study - Mahmoud Abbas; Jan de Jonge; Olaf Bettendorf (Life, 2023)
Background: Historically, cervical cytology has been the standard method for detecting dysplastic cervical changes. However, extensive research has established that human papillomavirus (HPV) infection is a primary cause of these changes, necessitating a shift in screening and preventive strategies towards the molecular detection of high-risk HPV subtypes. To combat HPV infection, prophylactic vaccines have been developed, including the nonavalent, quadrivalent, and bivalent vaccines. An essential criterion for an effective HPV vaccine is to provide comprehensive coverage against the most prevalent high-risk HPV types associated with cervical cancer, ensuring optimal efficacy in preventing cervical lesions. Long-term protection against these types is crucial for effective prevention strategies; Material and Methods: A cohort of 210,510 women’s samples was included in the analysis conducted within one year of implementing a screening program in Germany. The screening program involved the molecular detection of high-risk HPV subtypes, targeting specific age groups. The cohort comprised 63,710 women below 35 years of age and 146,800 women aged 35 years and above. The selection of high-risk HPV subtypes followed the guidelines provided by Becton-Dickinson. This study focused exclusively on cases with a documented history of vaccination, which were categorized into two main groups: Group I consisted of vaccinated individuals under 35 years old (12,765 cases), while Group II comprised vaccinated individuals aged 35 years and above (296 cases); Results: The HPV types HPV56/59/66 were found to be widely distributed across all age groups, with certain age groups exhibiting a higher incidence compared to HPV16 and HPV18. Similarly, HPV35/39/69, along with HPV31 and HPV45, were also observed to have a broad distribution among women. The incidence of high-grade squamous intraepithelial lesions (HSIL), including both CIN2 and CIN3, varied between 0.076% and 0.5% across all age groups, regardless of the individuals’ vaccination status; Aim of the study: Our study provides valuable insights into the distribution, incidence, and prevalence of various high-risk HPV subtypes, including HPV56/59/66, HPV33/58, HPV35/39/68, and HPV45, in relation to precancerous cervical lesions. These subtypes are not adequately covered by the currently available HPV vaccines. Addressing the discrepancies between the prevalent HPV subtypes and existing vaccines is crucial in developing an ideal HPV vaccine that offers comprehensive protection. Tailoring screening programs and vaccination strategies to the local distribution of HPV subtypes is essential for effective prevention. By raising awareness and implementing targeted preventive measures, including vaccination, we can significantly reduce the incidence of precancerous and cancerous cervical lesions.